2019
DOI: 10.3390/molecules24061078
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of Rosmarinic Acid Enhances its in vitro Antitumor, Antimicrobial and Antiprotozoal Properties

Abstract: On its own, rosmarinic acid possesses multiple biological activities such as anti-inflammatory, antimicrobial, cardioprotective and antitumor properties, and these are the consequence of its ROS scavenging and inhibitory effect on inflammation. In this study, two quaternary phosphonium salts of rosmarinic acid were prepared for the purpose of increasing its penetration into biological systems with the aim of improving its antimicrobial, antifungal, antiprotozoal and antitumor activity. The synthetized molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Cryptochlorogenic acid was moderately effective against fungi, but rosmarinic acid was the weakest. Previous studies reported moderate-to-low antimicrobial activities for rosmarinic acid [86,87] and naringin [88], and high antibacterial activities have been reported for chlorogenic acid (cryptochlorogenic acid derivatives) from Mammillaria extracts [4,89]. Chlorogenic acid displayed fungicidal activities against other pathogenic fungi such as Fusarium solani, Sclerotinia sclerotiorum, and Botrytis cinerea [90], and caffeic acid showed strong antibacterial and antifungal activities against several bacterial strains [2].…”
Section: Discussionmentioning
confidence: 99%
“…Cryptochlorogenic acid was moderately effective against fungi, but rosmarinic acid was the weakest. Previous studies reported moderate-to-low antimicrobial activities for rosmarinic acid [86,87] and naringin [88], and high antibacterial activities have been reported for chlorogenic acid (cryptochlorogenic acid derivatives) from Mammillaria extracts [4,89]. Chlorogenic acid displayed fungicidal activities against other pathogenic fungi such as Fusarium solani, Sclerotinia sclerotiorum, and Botrytis cinerea [90], and caffeic acid showed strong antibacterial and antifungal activities against several bacterial strains [2].…”
Section: Discussionmentioning
confidence: 99%
“…As stated by Mahboob et al [34], the acanthamoebicidal effect of Lonicera japonica flower, which evoked a significant reduction of trophozoite viability, depends mostly on the major compound form the extract, that is chlorogenic acid. According to Bittner Fialová, rosmarinic acid and its derivates appeared to be promising anti-Acanthamoeba agents with the EC 50 values between 5.6 ± 0.3 mM and 19.1 ± 0.4 mM [35]. The biological study of the Passiflora spp.…”
Section: Figurementioning
confidence: 99%
“…However, we have not evaluated the interaction of the individual secondary metabolites contained in the Lycopus infusions with the cell walls of the mentioned microbes. Concerning the antibacterial activity of the examined Lycopus infusions, we suggest that it could be bound to the presence of RA, which even in solo has excellent antimicrobial activity [27][28][29][30].…”
Section: Discussionmentioning
confidence: 90%